1992
DOI: 10.1089/hum.1992.3.2-137
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cell-Free Retroviral Vector Preparations for Transduction of Cells from the Marrow of Chronic Phase and Blast Crisis Chronic Myelogenous Leukemia Patients and from Normal Individuals

Abstract: Marrow cells were exposed to the LNL6 or G1N safety-modified variants of the N2 retrovirus, which contain the G418 bacterial resistance gene neo. The frequency of acquisition of the G418 resistance phenotype following exposure to LNL6 or G1N was compared among hematopoietic progenitor cells from the marrow of patients with chronic phase chronic myelogenous leukemia (CML), blast crisis CML, or from nonleukemic individuals. Under the conditions of our experiments, the myeloid committed progenitor cells from 3 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Our instkution has had experience with transplantation with the CD34 selected cells. We have seen recovery of the absolute neutrophil count to 500/cu mm in 10, 14, 14, and 17 days in breast cancer patients and 14,17,18,18,24, and 27 in advanced CML patients who have been transplanted with CD34 selected peripheral blood and martOW cells. The University of Denver has observed an average of 17 days to 500 neutrophils/cu mm in advanced breast cancer patients.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our instkution has had experience with transplantation with the CD34 selected cells. We have seen recovery of the absolute neutrophil count to 500/cu mm in 10, 14, 14, and 17 days in breast cancer patients and 14,17,18,18,24, and 27 in advanced CML patients who have been transplanted with CD34 selected peripheral blood and martOW cells. The University of Denver has observed an average of 17 days to 500 neutrophils/cu mm in advanced breast cancer patients.…”
Section: Introductionmentioning
confidence: 74%
“…Anderson, and have at the moment three protocols approved by the NIH Recombinant DNA Advisory Committee, and one protocol FDA-approved and ongoing at the M.D. Anderson Cancer Center at this time (16)(17)(18)(19). We have shown in oitt own laboratory that we can achieve ttansduction frequencies in the 1-5% range even with the normal hematopoietic progenitor cells (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous in vivo studies have used retroviral transduction in conjunction with bone marrow transplantation in murine models [1,[10][11][12][13], and in larger animal models including dogs [14][15][16][17] and Rhesus monkeys [18,19]. Results of human gene therapy clinical tri-als for adenosine deaminase deficiency [20][21][22] and gene marking in cancer patients [23][24][25] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…61 ODN have also been introduced into cells by retroviral strategies. [62][63][64][65] Our group has demonstrated that following the introduction …”
mentioning
confidence: 99%